Digital agricultural technology in Egypt: Insights from app developers - Tarek, Abdallah; Abdelhadi, Ali; Karachiwalla, Naureen (International Food Policy Research Institute, 2025)
Digital technologies have rapidly reshaped agricultural systems worldwide, and Egypt is no exception. Over the past decade, the proliferation of smartphones, mobile internet, and low-cost digital tools has opened new channels through which farmers, traders, processors, and aggregators access information and services. Smartphone applications, websites, call centers, and SMS-based platforms now offer advice on crop management, weather and climate alerts, input and output price information, traceability tools, and digital marketplaces. For smallholder farmers—who make up the backbone of Egypt`s agricultural sector—these tools have the potential to reduce information frictions, improve decision-making, and increase productivity and profitability. For larger firms engaged in aggregation, processing, or export, digital platforms can streamline supply chains, enhance coordination, and improve quality assurance.